HUBUNGAN TINGKAT STRES DENGAN KUALITAS TIDUR - Anggarkusuma, Mario Valentino; Dinata, I Made Krisna; Juhanna, Indira Vidiari; Wahyuni, Nila (Essence of Scientific Medical Journal; Vol 22 No 2 (2025): Volume 22 No. 2 (November 2024 - Maret 2025) Essential: Essence of Scientific Medical Journal, 2025)
Introduction: Many people have experienced sleep quality disorders. This results in disrupted quality of life. In this modern era, stress is one of the main factors causing poor sleep quality. High-stress levels can negatively impact latency, duration, and efficiency of sleep habits. Method: This observational study used an analytical approach using the cross-sectional method. The data used were primary data from the PSQI questionnaire to see sleep quality and DASS-42 to determine stress levels. After that, the data were analyzed using the Chi-Square method.. Result: The results of this study indicate that there is a significant relationship between stress levels and sleep quality with the Chi-Square test showing a p-value of 0.003. Discussion: Stress is one of the causes of sleep disorders that are often not realized. When someone experiences stress, there is an increase in the levels of the hormones epinephrine, norepinephrine, and cortisol, resulting in a state of wakefulness and increased alertness in the central nervous system in stressful conditions. Not only that, this change also affects the Non-Rapid Eye Movement and Rapid Eye Movement sleep cycles, which results in someone often waking up at night accompanied by nightmares. Stress activates the SAM and HPA systems, which affect the production of the hormones melatonin, cortisol, ACTH, CRH, and catecholamines. Conclusion: This study concluded that there is a relationship between stress levels and sleep quality.   Keywords: sleep quality, stress levels, relationship